Are There Threshold Concepts Associated with Learning to Become ‘Interprofessional’ and What Are the Implications for Exploring Practice-Based Learning? - Howden, Stella (International Journal of Practice-based Learning in Health and Social Care, 2018)
Newly graduating health and social care professionals are expected to be able to work in ways that exemplify being interprofessional, that is, learning and working with others with an aim to improve collaboration and the quality of care. The threshold concepts framework (TCF) offers an approach to explore how to support students’ learning in relation to those elements of professional working. In particular, the TCF places focus on understanding how students navigate gateways or threshold concepts (TCs), which are viewed as learning experiences resulting in a transformed view of a discipline and of self: a transformation that is essential to development as a professional. This discussion piece draws upon a growing body of literature (grey literature, empirical, and theoretical work) to propose that there are TCs associated with learning to become interprofessional; for example, respect for interprofessional partnerships and person centred care. Building on the analysis of that work and the literature associated with interprofessional education, the discussion moves to consider how practice-based placements may be particularly rich sites for further exploration of becoming ‘interprofessional’ using the TCF.